SPECTROSCOPIC AND RADIATIVE PROPERTIES OF SM3+ DOPED SODIUM-LEAD-ZINC-LITHIUM-BORATE GLASSES - Donna Rajagukguk; Juniastel Rajagukguk; Pintor Simamora; Rappel Situmorang; Chayani Sarumaha; Widyaningrum Indrasari (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
The glasses with a composition of (65 - x) B2O3 – 5ZnO – 5Li2O – 15 Na2O – 10PbO – x Sm2O3 (x = 0.0; 0.05; 0.1; 0.5; 1.0; 2.0 and 4.0 mol.%) which has been prepared using the melt quenching technique (1100oC for 3 hour). The spectroscopic properties can be determined by investigating the absorption, excitation, and emission spectra of a glass sample. There are 14 centered absorption bands starting from 6H5/2. The excitation spectrum of the Sm3+ doped borate glasses was measured at the wavelength of 300-550 nm which is the strongest intensity (4F7/2 at 403 nm) used as the excitation wavelength to measure the glass emission spectrum. The emission peaks transition starts from 4G5/2. The Judd-Ofelt theory has been applied to the absorption spectrum of Sm3+ doped borate glass to estimate the intensity parameters (Ωλ, λ = 2, 4 and 6) which are then used to calculate the radiative properties. The energy of the optical bandgap is in the range 3.85-3.77 eV for direct transitions and 3.42 - 4.22 eV for indirect transitions. The decay times obtained were 3.42, 3.99, 3.98, 2.96, 1.67, 1.48 ms for 0.05 - 4.00 mol%. Using the CIE chromaticity diagram for borate glass it can be determined that the glass from this work has a high performance for use as an orange emitting material application.